DISCUSSION ON: Robust validation of trends and cycles in sea level and tidal amplitude in the Dutch North Sea - Le Bars, Dewi; de Valk, Cees; Keizer, Iris; Jüling, André; van de Wal, Roderik; Drijfhout, Sybren; Lambert, Erwin (Journal of Coastal and Hydraulic Structures, 2025)
No abstract